Lipid Nanoparticles and Their Hydrogel Composites for Drug Delivery: A Review - Claire Desfrançois; Rachel Auzély; Isabelle Texier (MDPI AG, 2018)
Several drug delivery systems already exist for the encapsulation and subsequent release of lipophilic drugs that are well described in the scientific literature. Among these, lipid nanoparticles (LNP) have specifically come up for dermal, transdermal, mucosal, intramuscular and ocular drug administration routes in the last twenty years. However, for some of them (especially dermal, transdermal, mucosal), the LNP aqueous dispersions display unsuitable rheological properties. They therefore need to be processed as semi-solid formulations such as LNP-hydrogel composites to turn into versatile drug delivery systems able to provide precise spatial and temporal control of active ingredient release. In the present review, recent developments in the formulation of lipid nanoparticle-hydrogel composites are highlighted, including examples of successful encapsulation and release of lipophilic drugs through the skin, the eyes and by intramuscular injections. In relation to lipid nanoparticles, a specific emphasis has been put on the LNP key properties and how they influence their inclusion in the hydrogel. Polymer matrices include synthetic polymers such as poly(acrylic acid)-based materials, environment responsive (especially thermo-sensitive) polymers, and innovative polysaccharide-based hydrogels. The composite materials constitute smart, tunable drug delivery systems with a wide range of features, suitable for dermal, transdermal, and intramuscular controlled drug release.